The use of connective tissue growth factor mimics for flexor tendon repair. Issue 12 (25th February 2022) - Shen, Hua; Tarafder, Solaiman; Park, Gayoung; Qiu, Jichuan; Xia, Younan; Lee, Chang H.; Gelberman, Richard H.; Thomopoulos, Stavros
Abstract: Intrasynovial flexor tendon lacerations of the hand are clinically problematic, typically requiring operative repair and extensive rehabilitation. The small‐molecule connective tissue growth factor (CTGF) mimics, oxotremorine M (Oxo‐M) and 4‐PPBP maleate (4‐PPBP), have been shown to improve tendon healing in small animal models by stimulating the expansion and differentiation of perivascular CD146+ cells. To enhance intrasynovial flexor tendon healing, small‐molecule CTGF mimics were delivered to repaired canine flexor tendons via porous sutures. In vitro studies demonstrated that Oxo‐M and 4‐PPBP retained their bioactivity and could be released from porous sutures in a sustained manner. However, in vivo delivery of the CTGF mimics did not improve intrasynovial tendon healing. Histologic analyses and expression of tenogenic, extracellular matrix, inflammation, and remodeling genes showed similar outcomes in treated and untreated repairs across two time points. Although in vitro experiments revealed that CTGF mimics stimulated robust responses in extrasynovial tendon cells, there was no response in intrasynovial tendon cells, explaining the lack of in vivo effects. The results of the current study indicate that therapeutic strategies for tendon repair must carefully consider the environment and cellular makeup of the particular tendon for improving the healing response.